Advances in Bionanomaterials Selected Papers from the 2nd Workshop in Bionanomaterials, BIONAM 2016, October 4-7, 2016, Salerno, Italy - Piotto, Stefano; Rossi, Federico; Concilio, Simona; Reverchon, Ernesto; Cattaneo, Giuseppe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on multidisciplinary research focusing on the analysis, synthesis and design of bionanomaterials. It merges the biophysicists', the biochemists' and bioengineers' perspectives, covering the study of the basic properties of materials and their interaction with biological systems, the development of new devices for medical purposes such as implantable systems, and new algorithms and methods for modeling the mechanical, physical or biological properties of biomaterials. The different chapters, which are based on selected contributions presented at the second edition of BIONAM, held on October 4-7, 2016, in Salerno, Italy, cover both basic and applied research. This includes novel synthetic strategies for nanomaterials, as well as the implementation of bio- and smart materials for pharmacological and medical purposes (e.g. drug delivery, implantable systems), environmental applications, and many others. The book provides a broad audience of academic and professionals witha comprehensive, timely snapshot of the field of biomaterials. Besides offering a set of innovative theories together with the necessary practical tools for their implementation, it also highlights current challenges in the field, thus fostering new discussions and possible future collaborations between groups with different backgrounds.
Part I: Nanomaterials Engineering -- Part II: Nanomaterials Engineering -- Part III: Applications of Bionanomaterials.
Keywords: Biomedical engineering; Biomaterials; Chemistry, Technical; Bioinformatics; Biomedical Engineering and Bioengineering; Biomaterials; Industrial Chemistry; Computational and Systems Biology